Genome-wide identification and expression analysis of EPF/EPFL gene family in Populus trichocarpa - Liu, Sha; Chen, Ting; Li, Xin; Cui, Junjun; Tian, Yinshuai (Frontiers in Genetics, 2024)
The Epidermal Patterning Factor/EPF-like (EPF/EPFL) family encodes a specific type of secreted protein in plants and plays an important role in plant growth and development, especially in the process of morphogenesis. To investigate the characteristics of EPF/EPFL gene family members and their regulatory functions in stomatal development of Populus trichocarpa, a total of 15 EPF/EPFL family genes were identified. Then the gene structure, chromosome location, phylogenetic relationship, protein conserved domain and gene expression profile were analyzed.According to phylogenetic analysis, PtEPF/EPFL can be classified into four groups.The gene structure and protein conservation motifs within the EPF family indicate the high conservation of the PtEPF/EPFL sequence. The promoter region of PtEPF/EPFL was found to contain cis-elements in response to stress and plant hormones. In addition, RT-qPCR results indicated that the PtEPF/EPFL have a differentially expressed in different tissues. Under drought stress treatment, a substantial up-regulation was observed in the majority of PtEPF/EPFL members, suggesting their potential involvement in drought response. These results provide a theoretical basis for future exploration of the characteristics and functions of more PtEPF/EPFL genes.